UNDERSTANDING USER EXPERIENCE OF AN OPEN DESIGN-CLOTHING PRODUCT - Perez, Iana Uliana [UNESP] (2022)
Few studies related open design to the clothing sector, but none explored how users would experience it. The study reported here aimed to investigate how people with some or without prior sewing knowledge-advanced and amateur users – experience an open design-clothing product. Following four fashion design heuristics, a garment was created and distributed as DIY kits among advanced and amateur users. Data were collected in two stages: assembly and per-sonalization. The results indicate that although skills play a significant role during assembly, other factors, like cross-generational differences and personal taste, influence how users experience an open design product. Furthermore, the study shows that given the necessary support, the open design can be used by a heterogeneous public, amplifying the participation of users with little or without prior sewing skills in clothing co-creation.